Endoplasmic reticulum stress contributes to insulin resistance in Hashimoto’s thyroiditis - Qing Zhou; Li Yong Zhang; Xue Lin Gao; Chao Chun Zou; Hui Liu (Endocrine Connections)
Hashimoto’s thyroiditis (HT) is one of the most common autoimmune disorders. Patients with HT are more likely to be affected by insulin resistance, even euthyroid individuals. Endoplasmic reticulum (ER) stress is related to the pathogenesis of several immunological diseases, such as HT. Thus, the aim of the present study was to explore the potential mechanism and effect of HT on insulin resistance in HT model mice in vivo and to assess the role of ER stress in this process. In this study, euthyroid HT model mice were established by simultaneously giving high amounts of iodine in drinking water and twice subcutaneously injecting thyroglobulin emulsified with Freund’s adjuvant. HT mice were treated with or without 4-phenylbutyric acid (4-PBA), an inhibitor of ER stress. We detected increased protein expression of binding immunoglobulin protein (Bip), activating transcription factor 6 (ATF6), and upregulated phospho-inositol-requiring enzyme 1 (IRE1) and phospho-c-Jun N-terminal kinase (JNK) in the thyroid tissue and adipose tissue of HT mice. In addition, HT mice exhibited impaired insulin sensitivity, decreased insulin receptor substrate 1 (IRS-1) tyrosine phosphorylation and protein kinase B (AKT) phosphorylation in adipose tissue, but these effects were alleviated by 4-PBA. Moreover, HT mice had higher serum tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) levels than control mice. Similarly, the ER stress inhibitor 4-PBA significantly decreased TNF-α and IL-6 levels compared with those in HT mice. These findings suggest that HT is related to the development of insulin resistance, and that the mechanism may involve ER stress.